A “Bottom-Up” Approach to Aetiological Research in Autism Spectrum Disorders - Unwin, Lisa M.; Maybery, Murray; Wray, John; Whitehouse, Andrew (Frontiers in Human Neuroscience, 2013)
Autism Spectrum Disorders (ASD) are currently diagnosed in the presence of impairments in social interaction and communication, and a restricted range of activities and interests. However, there is considerable variability in the behaviours of different individuals with an ASD diagnosis. The heterogeneity spans the entire range of IQ and language abilities, as well as other behavioural, communicative and social functions. While any psychiatric condition is likely to incorporate a degree of heterogeneity, the variability in the nature and severity of behaviours observed in ASD is thought to exceed that of other disorders. The current paper aims to provide a model for future research into ASD subgroups. In doing so, we examined whether two proposed risk factors – low birth weight (LBW), and in-utero exposure to selective serotonin reuptake inhibitors (SSRIs) – are associated with greater behavioural homogeneity. Using data from the Western Australian Autism Biological Registry, this study found that LBW and maternal SSRI use during pregnancy were associated with greater sleep disturbances and a greater number of gastrointestinal complaints in children with ASD, respectively. The findings from this ‘proof of principle’ paper provide support for this 'bottom-up' approach as a feasible method for creating homogenous groups.